Teacher Preparation Programmes for ECCE - YADAV, PADMA (THE PRIMARY TEACHER, 2015)
Effective preparation of teachers for Early Childhood Care and Education (ECCE) is critical to the issue of quality of ECCE, especially since its focus is on a play-based, childcentered methodology which requires specialised skills and knowledge to equip the teacher to address specific contextual needs of every child. The National Policy on Education (1986) viewed ECCE as a crucial input in the context of human resource development and as a feeder and support programme for primary education. The ECCE has not yet been accorded the status of a fundamental right, nor is it in the ladder of school education system however it has found a place in RTE 2009 which says “With a view to prepare children above the age of three years for elementary education and to provide ECCE for all children until they complete the age of six years, the appropriate government may make necessary arrangement for providing free pre school education for such children” (Section 11, RTE Act, 2009). However, on 27 September 2013 Government of India (Ministry of Women and Child Development)after due consideration and approval passed a resolution and adopted National Early Childhood Care and Education (ECCE) Policy to promote inclusive, equitable and contextualised opportunities for promoting optimal development and active learning capacity of all children below 6 years of age.